Effect of topical application of adrenaline on Schlemm canal, trabecular meshwork and intraocular pressure - Ye, Meng; Chen, Zhiqi; Li, Mu; Chen, Wei; Zhang, Hong; Wang, Junming (Medicine (Baltimore), 2019)
To measure changes in the sizes of Schlemm canal (SC) and trabecular meshwork (TM) in healthy individuals before and after topical application of 1% adrenaline at 15, 45, and 90 minutes using anterior segment optical coherence tomography (ASOCT). Anterior chamber angle imaging of the nasal and temporal regions of the right eyes was performed with anterior segment optical coherence tomography (ASOCT) before and after topical application of 1% adrenaline at 15, 45, and 90 minutes. The diameter and area of SC, width and thickness of TM, anterior chamber depth (ACD) and pupil diameter (PD) were measured with ASOCT images. Intraocular pressure (IOP) was also recorded simultaneously. A total of 15 healthy individuals were enrolled and included 7 male subjects and 8 female subjects; Compared with the parameters before intervention, both the SC diameter and area in the 2 quadrants increased after the application of adrenaline at the 3 time points (P < .05). The TM width increased after medication (P < .05). IOP decreased significantly after application (P < .05). There were no statistically significant changes in TM thickness, ACD, and PD at any point of time (P > .05). Topical application of 1% adrenaline in eye led to decrease in IOP with the SC diameter and area as well as the TM width increased after medication. While the TM thickness, ACD, PD seemed to remain constant.